A comparative study on culture-specific and cross-cultural aspects of intercultural relations in Hungary, Serbia, Czech Republic, and Germany - Genkova, Petia; Herbst, Jonathan; Schreiber, Henrik; Rašticová, Martina; Poor, Jozsef; Veresné, Klara Valentinyi; Suhajda, Csilla; Viszetenvelt, Andrea; Bjekic, Jovana (Frontiers in Psychology, 2022)
The ability, will, and belief that it is possible to deal effectively with members of other cultural/ethnic groups are still gaining importance all over the world. However, the majority of studies on intercultural relations focuses on Western Europe and the United States, applying constructs and theories that replicate a western-centered worldview. As a consequence, it is unclear whether established measures for intergroup attitudes and intercultural competence may be applied in Eastern European countries and to what extent they display comparable ideas, thoughts, and feelings. The current study thus explores cross-cultural commonalities and differences in established measures of ethnic identity, prejudice, acculturation strategies, intercultural intelligence, and multicultural personality. Therefore, we compare the scale structure, difficulty, and sensitivity in samples from Germany and the Eastern European countries Hungary, Serbia, and the Czech Republic (etic-perspective), as well as the culture-specific conceptions of said concepts (emic-perspective). Results show that the investigated scales do not work comparably across German and Eastern European samples. Differences might be rooted in variations of underlying thinking patterns and connotations of single expressions. Those variations are likely to be related to the constant individual societal and historical developments of cultures, shaping the way individuals think and talk about cultural diversity. Future studies are encouraged to consider culture-specific and generalizable aspects of constructs when conducting cross-cultural research on intercultural relations.